Crystal Structure, Spectroscopic and Thermal Investigations of a New 4-Ammonio-2,2,6,6-tetramethylpiperidinium Tetrachlorozincate(II) - M. El Glaoui; M. L. Mrad; E. Jeanneau; C. Nasr (E-Journal of Chemistry, 2010)
The new complex of Zn(II) with 4-ammino-2,2,6,6-tetramethylpiperidine, [C9H22N2]ZnCl4, has been prepared and characterized by various physicochemical studies. This compound crystallizes in the monoclinic system, with the space group P21/c and the following cell parameters: a = 9.8682(7), b = 7.5164(5), c = 21.019(2) Å, β = 99.003 (7)°, V = 1539.8(2) Å3 and Z = 4. The crystal structure was solved and refined to R = 0.024 using 3070 reflections. The atomic arrangement can be described by slightly distorted tetrahedral ZnCl42- anions and 4-ammmonio-2,2,6,6-tetramethylpiperidinium cations holding together by different interactions. The four chlorine atoms of the ZnCl42- tetrahedron are acting as acceptors of hydrogen bonds. The crystal packing is influenced by cation-to-anion N-H…Cl and C-H…Cl hydrogen bonds leading to open framework architecture.